1977
DOI: 10.1530/jrf.0.0510023
|View full text |Cite
|
Sign up to set email alerts
|

Binding of LH and FSH to porcine granulosa cells during follicular maturation

Abstract: The uptake of 125I-labelled LH by equal numbers of granulosa cells from small, medium or large follicles was greater by cells from large follicles. In contrast, granulosa cells obtained from small follicles bound much more 125I-labelled FSH per cell than did cells obtained from medium and large follicles. Competition studies with unlabelled hormones indicated that porcine granulosa cells have specific receptors for LH and FSH. The addition of diethylstilboestrol enhanced the binding of 125I-labelled LH and inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
22
0

Year Published

1979
1979
1994
1994

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(27 citation statements)
references
References 16 publications
5
22
0
Order By: Relevance
“…PGF-2a is luteolytic in pigs when given late in the cycle, and in other species leads to loss of luteal LH receptors (Grinwich, Ham, Hichens & Behrman, 1976a;Grinwich, Hichens & Behrman, 1976b (Goldenberg, Bridson & Köhler, 1972;Veldhuis, Klase & Hammond, 1981) and of stilboestrol on binding of LH by isolated porcine granulosa cells (Nakano, Akahori, Katayama & Tojo, 1977). These two mechanisms (via the uterus and direct) are not necessarily mutually exclusive and both may be involved in maintaining luteal function in early pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…PGF-2a is luteolytic in pigs when given late in the cycle, and in other species leads to loss of luteal LH receptors (Grinwich, Ham, Hichens & Behrman, 1976a;Grinwich, Hichens & Behrman, 1976b (Goldenberg, Bridson & Köhler, 1972;Veldhuis, Klase & Hammond, 1981) and of stilboestrol on binding of LH by isolated porcine granulosa cells (Nakano, Akahori, Katayama & Tojo, 1977). These two mechanisms (via the uterus and direct) are not necessarily mutually exclusive and both may be involved in maintaining luteal function in early pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Oestrogens, which are luteotrophic in the intact sow (Kidder, Casida & Ruimmer, 1955;Gardner, First & Casida, 1963), are produced by the placenta in this species and increase at Days 25 and 70 (Fèvre, Leglise & Rombauts, 1968 (Goldenberg, Bridson & Köhler, 1972) and stimulate 125I-labelled LH binding to dispersed granulosa cells (Nakano, Akahori, Katayama & Tojo, 1977) and luteal membranes (Garverick, Polge & Flint, 1982) in the sow. Oestrogens also play a role in prolactin receptor regulation, as demonstrated in pig granulosa cells at the time of luteinization (Hammond & Krall, 1979).…”
Section: Sowmentioning
confidence: 96%
“…Evans et al (1981) reported that granulosa cells responded to FSH by increasing progesterone production when cultured for 24 h, but that they also responded to LH. It is important to note that the theca cells used for culture in this study by Evans et (Nakano et al, 1977;Lee, 1978;Lindsey and Channing, 1979 (Morley et al, 1989). It has recently been shown that pure FSH can activate paracrine signalling in granulosa cells, which affects androgen production in thecal and interstitial cells (Smyth et al, 1993 …”
Section: Introductionmentioning
confidence: 94%
“…These differences can be summarized as follows: (1) porcine theca cells can synthesize Clg steroids, but granulosa cells cannot without the addition of extrinsic aromatizable androgens (Evans et al, 1981;Tsang et al, 1985Tsang et al, , 1987; (2) porcine theca cells can synthesize C19 steroids, but granulosa cells cannot (Short, 1962;Bjersing and Carstensen, 1967;Younglai and Short, 1970;Fortune and Armstrong, 1978); and (3) FSH binds to granulosa cells, but not to theca cells. FSH does not therefore affect the steroidogenesis of theca cells (Nakano et al, 1977;Fay and Douglas, 1987).…”
Section: Introductionmentioning
confidence: 99%